2009
DOI: 10.1590/s1678-77572009000100006
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pulse-delay curing on sorption and solubility of a composite resin

Abstract: The purpose of this study was to evaluate the sorption and solubility of a composite resin (TPH3; Dentsply) cured with halogen light due to different storage media and curing modes. The methodology was based on the ISO 4049 standard. Two independent groups were established according to the storage time (7 days-G1; 60 days-G2). A stainless steel mould (2 mm x 8 mm ø) was used. The selected curing modes were: I (Conventional - C): 40s - 600 mW/cm2; II (Pulse I - PD): 3 s - 200 mW/cm2 + 2 min (delay) + 39 s - 600… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 25 publications
(49 reference statements)
2
25
1
6
Order By: Relevance
“…18 In other studies, it has been suggested that negative values may be the result of hydrogen bonds connecting the absorbed water molecules to polar groups of the polymer chains, which cannot be removed entirely. 31,32 As a result, Filtek Z250 showed higher water sorption values in all curing modes when compared with bulkfill composites. In terms of water solubility, the SonicFill bulk-fill composite showed the highest value among the groups, so that the null hypothesis was rejected.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…18 In other studies, it has been suggested that negative values may be the result of hydrogen bonds connecting the absorbed water molecules to polar groups of the polymer chains, which cannot be removed entirely. 31,32 As a result, Filtek Z250 showed higher water sorption values in all curing modes when compared with bulkfill composites. In terms of water solubility, the SonicFill bulk-fill composite showed the highest value among the groups, so that the null hypothesis was rejected.…”
Section: Discussionmentioning
confidence: 95%
“…Negative solubility results have also been reported in other studies. 18,31,32 In some studies, these negative values have been explained by possible hydrolytic chemical reactions that result in the formation of metal hydroxides on the filler surface. 18 In other studies, it has been suggested that negative values may be the result of hydrogen bonds connecting the absorbed water molecules to polar groups of the polymer chains, which cannot be removed entirely.…”
Section: Discussionmentioning
confidence: 99%
“…Two possible explanations for the negative solubility values are assumed. The first one was that the absorbed water during storage period may have not been completely eliminated, and consequently mass gain was obtained [27, 30, 32]. Secondly, the volatile smoke compounds may be linked to the adhesive systems specimens and led to increase the mass values.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of water sorption and solubility have mainly been conducted in water [18, 19, 22, 24], artificial saliva [25], lactic acid [26], different pH beverages [23], ethanol, and chloroform [27]. To date, the ability of volatile compounds released during the cigarette combustion to affect the water sorption and solubility of resin-based materials is not yet described.…”
Section: Introductionmentioning
confidence: 99%
“…Este fato também está de acordo com o trabalho de Lopes et al (2008), que também encontraram valores de solubilidade negativos, o que indica que o cimento é mais sensível à sorção de água levando ao ganho de massa, que poderia mascarar a solubilidade real. Isso não significa que não ocorreu solubilidade, mas que a sorção de água foi maior que a solubilidade [22] . Tanto a sorção quanto a solubilidade são dependentes da composição química dos materiais resinosos.…”
Section: Resultsunclassified